2012
DOI: 10.1007/s10856-012-4768-2
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, safety and pharmacokinetic study of hepatic administration of drug-eluting beads loaded with irinotecan (DEBIRI) followed by intravenous administration of irinotecan in a porcine model

Abstract: Irinotecan eluting embolization beads (DEBIRI) are currently being evaluated in the clinic for the treatment of colorectal cancer metastases to the liver. The aim of this study was to determine the safety and pharmacokinetics associated with two cycles of hepatic embolization using DEBIRI followed by intravenous administration of irinotecan. Pigs were embolized with DEBIRI (100–300 μm, 100 mg dose, n = 6) and blood samples taken over 24 h to determine plasma levels of irinotecan and SN-38 metabolite and for ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
2
11
1
Order By: Relevance
“…Accordingly, the C max was significantly higher for DC Bead M1. This fast initial elution of irinotecan has been previously described for DEBIRI (16). In a rabbit VX2 liver tumor model, Rao et al (18) observed the highest irinotecan plasma concentration after 10 minutes.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Accordingly, the C max was significantly higher for DC Bead M1. This fast initial elution of irinotecan has been previously described for DEBIRI (16). In a rabbit VX2 liver tumor model, Rao et al (18) observed the highest irinotecan plasma concentration after 10 minutes.…”
Section: Discussionsupporting
confidence: 70%
“…However, Lewis et al (16) applied a higher total dose (100 mg irinotecan) than used in the present study. Even with this higher dose of irinotecan, SN-38 levels were below the quantification level in many cases (16).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations